INNOVATIVE ENERGY SOLUTION: SUSTAINABLE ENERGY GENERATION VIA FORESTRY WASTE INCINERATION IN RANKINE CYCLE POWER PLANT - Scoculi de Lira, Gilvana; Jacob-Furlan, Beatriz; Silva Ribeiro Gonçalves, Rafael; Miléo Taher, Dhyogo; Langer, Marcelo; Augusto Ferraz, Fernando; Balmant, Wellington; Viriato Coelho Vargas, José; Bellin Mariano, André (Revista de Engenharia Térmica, 2024)
The use of organic solid waste for energy generation has become a promising and sustainable solution to address environmental issues, particularly those related to fossil fuel consumption. Producing energy from forest biomass offers a viable and eco-friendly alternative, aiming to reduce greenhouse gas (GHG) emissions. A key factor for the sustainable production and supply of bioenergy is the abundant availability of suitable raw materials. Among these, forestry pruning waste stands out as a significant resource, often poorly managed and improperly disposed of. An environmentally responsible way to utilize these residues is through incineration, using the resulting hot gases from combustion for energy generation. The primary goal of this study was to quantify the energy generation potential from the forestry pruning waste of UFPR. To achieve this, the organic waste from UFPR was chemically characterized through Proximate Analysis, along with determining the higher heating value and moisture content. A mathematical model was developed to quantify the generation of electrical energy, simulating the steady-state operation of the incineration system. Additionally, a mathematical model of the Rankine cycle plant was created to predict the necessary thermal exchange areas in the plant. The analyses of the collected samples showed heterogeneity, with low ash content at 0.76% and moisture content ranging from 10.67% to 16.80%, but an average high higher heating value of 19.39 MJ.kg-1. The mathematical model predicted that these residues could be sustainably used for electricity generation, with a power output of 54.28 kW. The chemical analysis results led to optimization in the thermal exchange areas of the Rankine cycle plant, facilitating the efficient utilization of hot gases produced from the incineration of these forestry residues.